Advancements and Prospects in Personalized Navigation Systems for Knee Arthroplasty: A Literature Review - Sulyma, O.M.; Chornyi, V.S.; Kozik , Ye.V. (TERRA ORTHOPAEDICA, 2025)
Introduction. Traditional methods of knee arthroplasty are based on mechanical alignment, which ensures long-term component survival but does not always meet patients’ functional needs. Recent studies indicate that personalized alignment approaches, such as kinematic and functional alignment, can improve functional outcomes and reduce complication rates. These methods consider the natural axes of movement and the anatomy of the knee joint, contributing to the restoration of joint anatomy and function. Individualized navigation systems represent a modern approach to knee arthroplasty using three-dimensional preoperative models based on CT or MRI. This method improves the accuracy of fitting the prosthesis components, considering the patient’s individual anatomical features and biomechanical parameters. Objective. The objective of this literature review is to analyze the literature on using advanced navigation systems and evaluate their effectiveness, advantages, and prospects in personalizing knee joint arthroplasty. Material and Methods. Using PubMed, Scopus, and Web of Science databases, we reviewed 22 scientific studies on various navigation systems for knee joint arthroplasty. Studies were selected based on patient numbers, statistical significance, clear inclusion and exclusion criteria, and availability of objective treatment outcome data. This allowed for a detailed analysis and comparison of different navigation methods. Results. Total knee arthroplasty (TKA) is one of the most effective surgical treatments for knee osteoarthritis. However, the accuracy of prosthesis implantation remains a critical factor for the long-term success of the surgery. Deviations in placement can lead to increased wear of components and a higher risk of complications. Traditionally, standard tools and techniques based on anatomical landmarks are used for prosthesis placement. In recent years, individualized navigation systems (INS) based on preoperative three-dimensional modeling of the patient’s individual anatomy have been introduced. INS aim to improve the accuracy of knee joint component placement, reduce time of surgery, and lower the risk of complications. Conclusions. The use of patient-specific surgical instruments and resection tools in primary and revision knee joint arthroplasty improves surgical and rehabilitation outcomes. This development allows for a 30% improvement in implant positioning accuracy and a 10% reduction in CO2 emissions. Standardizing research methods and increasing surgeon experience may contribute to a better understanding of the long-term benefits of individualized navigation systems in knee joint arthroplasty. Despite the identified advantages of INS, further research is needed to determine the long-term clinical outcomes and cost-effectiveness of these systems. The application of INS is especially important in cases of significant deformities and bone defects.